2017
DOI: 10.1159/000484026
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Mediated Expression of BMP-2 and BFGF in Bone Marrow Mesenchymal Stem Cells Combined with Demineralized Bone Matrix For Repair of Femoral Head Osteonecrosis in Beagle Dogs

Abstract: Background: This study investigated the effect of using adenovirus-mediated expression of bone morphogenetic protein 2 (Ad-BMP-2) and basic fibroblast growth factor (bFGF) in bone marrow mesenchymal stem cells (BMSCs) in combination with a demineralized bone matrix (DBM) to repair osteonecrosis of the femoral head (ONFH) in Beagle dogs. Methods: A total of 30 Beagle dogs were selected for the isolation of BMSCs, which were cultured and transfected with the recombinant adenovirus vector Ad-BMP2-bFGF-GFP (carryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…bFGF could stimulate cell motility via activating the FGFR1‐PI3K‐Rac1 pathway and promoted osteogenic differentiation through the activation of MAPK and smad‐dependent signaling pathway . The current application modalities of bFGF and BMP‐2 were designed to release the two factors at the same time . Our study confirmed that sequential application of bFGF and BMP‐2 showed more excellent effect in up‐regulating the osteogenic capability of PDLSCs when compared with the simultaneous application manner.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…bFGF could stimulate cell motility via activating the FGFR1‐PI3K‐Rac1 pathway and promoted osteogenic differentiation through the activation of MAPK and smad‐dependent signaling pathway . The current application modalities of bFGF and BMP‐2 were designed to release the two factors at the same time . Our study confirmed that sequential application of bFGF and BMP‐2 showed more excellent effect in up‐regulating the osteogenic capability of PDLSCs when compared with the simultaneous application manner.…”
Section: Discussionsupporting
confidence: 63%
“…Basing on current studies, combination of bFGF and BMP‐2 may have broad applications in bone regeneration medicine. It has been reported that the combination of bFGF and BMP‐2 could induce stem cells osteogenic differentiation . The current application of these two growth factors can be summarized to three types.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter risk was alleviated by rifampicin likely through enhancing P-gp activity [20], whereas glucocorticoid-induced ONFH was successfully prevented by treatment with Vitamin K2 [21]. Moreover, augment the expression of BMP-2 and BFGF in BMSCs promoted bone repair of ONFH [22]. These results suggest that multiple factors are involved in the therapeutic effects of BMSCs on ONFH, and additional treatment with drug or transgenic modification may promote their efficacy.…”
Section: Introductionmentioning
confidence: 99%